2015
DOI: 10.1162/jocn_a_00751
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Modulation in the Activity and Connectivity of Motor Cortex during the Repeated Generation of Movement Sequences

Abstract: It is not clear how the engagement of motor mnemonic processes is expressed in online brain activity. We scanned participants, using fMRI, during the paced performance of a finger-to-thumb opposition sequence (FOS), intensively trained a day earlier (T-FOS), and a similarly constructed, but novel, untrained FOS (U-FOS). Both movement sequences were performed in pairs of blocks separated by a brief rest interval (30 sec). We have recently shown that in the primary motor cortex (M1) motor memory was not expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 103 publications
(149 reference statements)
2
18
0
4
Order By: Relevance
“…Our results are limited to a relatively simple motor task and short-term training. Our training duration is compatible with respect to similar short-term learning studies reported in the literature (Gabitov et al, 2015;Mattar and Gribble, 2005). However, in short-term motor learning, there is a potential for bias from an unspecific arousal effect in the incongruent condition.…”
Section: Discussionsupporting
confidence: 84%
“…Our results are limited to a relatively simple motor task and short-term training. Our training duration is compatible with respect to similar short-term learning studies reported in the literature (Gabitov et al, 2015;Mattar and Gribble, 2005). However, in short-term motor learning, there is a potential for bias from an unspecific arousal effect in the incongruent condition.…”
Section: Discussionsupporting
confidence: 84%
“…The results for the trained hand have been reported previously (Gabitov et al . , ). The performance test for each condition included four consecutive blocks of 30 s in duration separated by rest intervals of 30 s. Before each test‐block, participants were asked to perform the movement sequence, and the block was initiated only after the FOS was accurately reproduced three times in a row.…”
Section: Methodsmentioning
confidence: 99%
“…The trained (left) hand was tested as well; the results are reported elsewhere (Gabitov et al . , ). The imaging session consisted of three consecutive runs for each sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a role for sleep, specifically SWS, was suggested in the selective maintenance and promotion of the dendritic spines relevant to task performance (Yang et al, 2014). Recent fMRI experiments suggest the possibility of a selective effect of an overnight consolidation interval in young human adults at the systems level as well (Gabitov et al, 2014(Gabitov et al, , 2015. Notably, the execution of a consolidated finger opposition sequence was characterized by a distinct dynamic pattern (repetition enhancement) in the contralateral M1 and, bilaterally in the medial-temporal lobes.…”
Section: Consolidation and Transformation In ''Non-declarative'' Memorymentioning
confidence: 99%